2021
DOI: 10.3389/fphys.2021.717187
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED: Abnormal Mitochondria-Endoplasmic Reticulum Communication Promotes Myocardial Infarction

Abstract: Myocardial infarction is characterized by cardiomyocyte death, and can be exacerbated by mitochondrial damage and endoplasmic reticulum injury. In the present study, we investigated whether communication between mitochondria and the endoplasmic reticulum contributes to cardiomyocyte death after myocardial infarction. Our data demonstrated that hypoxia treatment (mimicking myocardial infarction) promoted cardiomyocyte death by inducing the c-Jun N-terminal kinase (JNK) pathway. The activation of JNK under hypox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 81 publications
0
7
0
Order By: Relevance
“…During hypoxia-reoxygenation Fis1 stimulates SR-Ca 2+ release through interaction with BAP31, which, in turn, promotes Bax and Bak translocation to the mitochondria and the initiation of apoptosis ( Lu et al, 2010 ). In agreement with these studies, a recent article by Cheng et al, has shown that loss of the Fis-BAP31 crosstalk protects hearts from myocardial infarction by downregulating mitochondrial ROS production and c-Jun N-terminal kinase (JNK) pathway activation, thus inhibiting cardiomyocyte cell death ( Cheng et al, 2021 ).…”
Section: Inter-organelle Communication In I/rmentioning
confidence: 72%
“…During hypoxia-reoxygenation Fis1 stimulates SR-Ca 2+ release through interaction with BAP31, which, in turn, promotes Bax and Bak translocation to the mitochondria and the initiation of apoptosis ( Lu et al, 2010 ). In agreement with these studies, a recent article by Cheng et al, has shown that loss of the Fis-BAP31 crosstalk protects hearts from myocardial infarction by downregulating mitochondrial ROS production and c-Jun N-terminal kinase (JNK) pathway activation, thus inhibiting cardiomyocyte cell death ( Cheng et al, 2021 ).…”
Section: Inter-organelle Communication In I/rmentioning
confidence: 72%
“…As reported, artificial induction of MERCs only affected hepatocytes when animals developed obesity, leading to the conclusion that an increased number of MERCs and overweight cause the mitochondrial dysfunction that affects liver metabolism (Arruda et al, 2014). However, these results encountered some dissidence, because another study indicated that increased MERCs improves liver function (Tubbs et al, 2014), as it has been described in other tissues (Gutiérrez et al, 2014;Dia et al, 2020;Cheng et al, 2021). This discrepancy could be explained by several reasons: 1.…”
Section: Mitochondria-er Contacts In Hepatocytesmentioning
confidence: 98%
“…As already mentioned, the loss of interaction between the ER and mitochondria in cardiomyocytes increases with aging and heart disease, thereby decreasing mitochondrial function and altering cellular processes such as oxidative stress, autophagy and metabolic imbalance, consequently affecting the overall heart function (Murley and Nunnari, 2016;Gude et al, 2018). For instance, alterations in the ER-mitochondria interaction result in the progression of acute myocardial ischemia/reperfusion (I/R) (Cheng et al, 2021) and diabetic heart disease (Dia et al, 2020;Zhang et al, 2021a), due to ER and mitochondria stress, which ultimately decrease mitochondrial function (Gude et al, 2018). Mitochondrial Ca 2+ uptake is decreased in aged cardiomyocytes, and this has been associated with a decreased production of NADPH and increased generation of mitochondrial ROS.…”
Section: Mitochondria-er Contacts and Cardiomyocytesmentioning
confidence: 99%
“…BAP31, an ER protein, regulates intracellular calcium homeostasis and ER stress (90). Cheng et al (91) found that silencing Fis1/ BAP31 reduced mitochondrial fission and inhibited JNK activation, which led to a reduction in ROS and promoted cardiomyocyte survival.…”
Section: Myocardial Infarctionmentioning
confidence: 99%